The Craft of Dyers in the Medieval Islamic Mediterranean (9th–15th Centuries) - Akiniz, Sercan (Hitit İlahiyat Dergisi, 2025)
The medieval Islamic Mediterranean was a significant hub for textile dyeing, not only due to its technical achievements but also because of its economic and commercial networks that played a defining role across the region and beyond. Compared to their European counterparts, Islamic states historically had broader access to dyestuffs, positioning themselves as key nodes in both production and interregional dyeing networks. Historical sources indicate that dyeing was a widespread economic activity throughout the Islamic world, from Egypt to al-Andalus, from the Maghreb to Anatolia. This study examines dyeing centers in the medieval Islamic Mediterranean, the organizational structures of dyers, their economic and social status, and the legal frameworks regulating their profession. By integrating historical records, legal documents, futuwwa manuals, waqf deeds, and archaeological findings, this research provides a comprehensive analysis of the role of the dyeing industry in medieval Islamic societies. The primary research question of this study is how the dyeing profession was positioned within the socio-economic framework of medieval Islamic societies and how its operational mechanisms were structured. Furthermore, it evaluates the relationship between dyers and governing authorities, as well as the legal and institutional mechanisms that regulated their activities. Previous studies have predominantly focused on specific textile centers, the procurement of dyestuffs, or the technical aspects of dye production. However, there is a notable gap in the literature regarding the institutional, legal, and socio-economic regulations governing the dyeing craft. By examining the position of dyers within medieval Islamic craft organizations and the legal frameworks shaping their profession, this study aims to address this gap. Synthesizing legal texts with historical narratives and archaeological findings, it offers a holistic perspective on the historical development of the dyeing industry and its impact on Islamic economies. Methodologically, this research utilizes a range of primary sources, including legal treatises, travelogues, and historical and geographical accounts, alongside secondary studies. Legal sources provide valuable insights into regulations imposed on dyers, covering taxation, occupational oversight, and commercial disputes. Historical chronicles and travel narratives offer extensive descriptions of the geographical distribution and economic significance of dyeing centers. Waqfiyya archives present evidence regarding the locations of dye workshops and their contributions to local economies, while archaeological findings confirm the material evidence of dye production and practices. The integration of these diverse sources facilitates a multidisciplinary approach that combines historical, legal, and archaeological perspectives. This study demonstrates that the dyeing profession was deeply embedded in the economic and social fabric of medieval Islamic societies. It highlights the professional organization of dyers within different communities, ranging from futuwwa and Ahi brotherhoods to the later development of guilds. Futuwwa manuals emphasize the ethical and spiritual dimensions of the craft, identifying legendary figures as patrons of dyers. Additionally, Islamic legal sources underscore the regulatory role of the ḥisbah institution in overseeing the dyeing profession. Muḥtasibs were responsible for monitoring dye quality, ensuring compliance with professional standards, and preventing fraudulent practices. In this context, ḥisbah treatises and ihtisab laws are examined to delineate the professional obligations of dyers. Another key finding of this study challenges the prevailing notion that dyeing was an exclusively Jewish profession. This widely accepted perspective is critically analyzed, and the study establishes that dyeing was not confined to any particular religious or ethnic group. The research underscores the significant role of Muslim dyers and emphasizes that assessments of the profession must consider regional and demographic variations. In conclusion, this study directly addresses the dyeing craft, which has often remained overshadowed within medieval textile studies. By integrating historical, geographical, legal, and archaeological sources, it provides a broad evaluation that extends from the placement of dye workshops to professional regulations, quality control mechanisms, and consumer protection measures. The findings highlight that the dyeing industry did not develop arbitrarily but rather within the framework of specific legal and social regulations, demonstrating its multicultural and dynamic nature.